Research on Engineering Optimization Based on BIM Technology - Wang, Wen (Procedia computer science, 2025)
With the promulgation of national policies and the demand of market development, various industries actively carry out research based on BIM (Building Information Modelling) Technology + specialty and apply it to engineering construction. The application of BIM technology in geotechnical engineering provides a milestone technological change for the digital development of geotechnical engineering. In combination with the actual production needs, we will develop a digital platform based on BIM in geotechnical engineering, realize the digital platform for the whole process from exploration, design, construction and monitoring, assist enterprises to reduce costs and increase efficiency, and improve the professional status of the geotechnical industry in the construction field.